The non-linear dependence of 6СНВТ liquid crystal conductivity on the concentration of gold nanoparticles - Kovalchuk, O.V.; Kopčansky, P.; Timko, M.; Studenyak, I.P.; Kovalchuk, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Within the frequency range 10⁻¹…10⁶ Hz at the temperature 293 K, the effect of gold nanoparticles on the dielectric properties of the planar-oriented nematic liquid crystal 6СНВТ has been studied. The concentration of nanoparticles with the average diameter 3 to 5 nm was chosen as 0.01, 0.02 and 0.1 wt.%. It has been shown that for the frequencies less than 10 Hz, the dielectric properties of the samples can be described with the Debye dispersion. For the samples with the concentration of gold nanoparticles 0.1 wt.%, the time of relaxation has been estimated (4.7±0.5 s). It has been also shown that the conductivity of the liquid crystal depends non-linearly on the concentration of nanoparticles introduced into the liquid crystal. The greatest change in conductivity of the liquid crystal on the concentration of introduced gold nanoparticles has been obtained within the range of 0.01 to 0.02 wt.%. It has been assumed that the conductivity of 6СНВТ that depends non-linearly on the concentration of introduced gold nanoparticles is caused by the competing processes of ion desorption from the gold nanoparticles and of nanoparticle aggregation.